Analysis on Yields of Optimal Spaced and Broadcasted Grain Amaranth in Kabale Municipality. - Banyenzaki, Daglous (Kabale University, 2025)
The study was about to analyze yields of optimally spaced and broadcasted grain amaranth in Kabale municipality. The study had the following objectives; to assess the impact of different spacing arrangements on amaranth yield, and to compare the yield of amaranth produced between the spaced one and broadcasted grain amaranth. The study adopted a field experimental design. The experiment was carried out on the Kabale University farm.T he results of this study demonstrate that out of a total of 20 observations, the majority of roots, 75%, fall within the 1-4 length range, constituting 15 instances. Additionally, 25% of the roots in this method fall within the 5-8 length range, totaling 5 instances. In conclusion, the comparison between spaced plots and broadcasted plots across plant height, root length, and total weight distribution highlights the significant influence of planting methods on various parameters related to plant growth and productivity. Spaced plots exhibit greater variability in plant height, root length, and total weight distribution compared to broadcasted plots, indicating the potential benefits of adopting spacing methods in agricultural practices. The study recommended that; Assessing planting density is crucial in determining the optimal spacing between plants to maximize yield potential. Adjusting planting density based on crop requirements, environmental conditions, and available resources can help optimize plant growth and resource utilization, Paying close attention to root development is essential for ensuring optimal nutrient uptake and overall plant health. Regular monitoring of root length and exploration can provide insights into soil health and nutrient availability, allowing growers to adjust management practices accordingly.